Harvesting the Vibration Energy with BaTiO3@Graphene for the Piezocatalytic Degradation of Methylene Blue - Hou, Tian; Cao, Fang; Li, Meilin; Wang, Jinlong; Lv, Lingling (Journal of Environmental Science and Engineering Technology, 2020)
Piezocatalysis is a newly advanced oxidation process (AOP) which can be triggered by mechanical force to generate electric field, and then drives free charge carriers to participate redox reactions. In this work, reduced graphene oxide (rGO) is integrated with the widely used barium titanate (BTO) to regulate the surface free charges of composites. The piezocatalytic activity of integrated composite (BTO@rGO) is strongly related with the mass ratio of BTO and rGO. Driven by ultrasonic force, BTO@rGO can completely decompose methylene blue (MB) within 120 min when the mass ratio of BTO to rGO is 2:1, showing the best activity comparing with samples of other mass ratios (10:1, 5:1, and 1:1). The introduction of graphene facilitates the interface charge transfer to BTO, which is proved by peak shift information of Raman and X-ray photoelectron spectroscopy (XPS). The generated hydroxyl radical (.OH) is the active species participating in MB oxidation. This work not only gives a clear understanding of interface electron transfer mechanism but also sheds light on the construction of well-performed piezocatalysts.